Acoustic emission characteristics and damage constitutive model of fractured sandstone under uniaxial compression - Qiang Liu; Chao Pan; Lin Yan; Xuguang Wang; Shujian Li; Juncai Cao (Scientific Reports)
Abstract To investigate the statistical laws of acoustic emission energy (AEE) avalanche dynamics of sandstone under varying fracture lengths and dip angles, as well as to determine the relationship between acoustic emission (AE) parameters and damage variables, we studied the mechanical properties and AE characteristics of sandstone with a single fracture subjected to uniaxial compression with the aid of the Shimadzu AG-IS test system and the PCI-2 AE system. The AEE characteristics of fractured sandstone under load were analyzed based on the statistical method of avalanche dynamics, with emphasis on AEE distribution, aftershock sequence, and waiting time distribution. The Weibull distribution function that incorporates a correction coefficient β was employed to optimize the Weibull parameters based on the strain equivalent hypothesis theory, which led to the establishment of a statistical damage constitutive model for fractured rock. The results indicated that the peak strength of rock samples initially decreases and then increases with increasing fracture dip angle, and decreases with increasing fracture length. The AEE of the rock sample followed a power-law distribution, with a power-law index ranging from 1.62 to 1.81, which was independent of fracture length and dip angle. The aftershock sequence also adhered to a power-law distribution, whereas the waiting time exhibited a multi-power-law distribution. The proposed statistical damage constitutive model aligned more closely with the experimental curves compared to previous models that normalizes AEE.